(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Shoot of Triticum aestivum Linn. (Hindi Name- gehun, kanak, Sanskrit name- godhuma) is called as a wheat grass, belonging to family: Gramineae, which posses high chlorophyll content and essential vitamins, minerals, vital enzymes, amino acids, dietary fibers. Wheat grass has been shown to posses anti-cancer activity, anti-ulcer activity, antioxidant activity, anti-arthritic activity, and blood building activity in Thalassemia Major. It has been argued that wheat grass helps blood flow, digestion and general detoxification of the body. The major clinical utility of wheat grass in diseased conditions might be due to the presence of biologically active compounds and minerals in it and due to its antioxidant potential which is derived from its high content of bioflavonoids such as apigenin, quercitin, luteoline. Furthermore, indole compounds namely choline and laetrile present in it might be also responsible for its therapeutic potential. The presence of 70% chlorophyll, which is almost chemically identical to hemoglobin, in wheat grass makes it more useful in various clinical conditions involving hemoglobin deficiency and other chronic disorders. The present review article focuses onto various studies conducted on the use of wheatgrass in various disease conditions. Since very little clinical studies have been made on this very promising herbal drug, efforts are needed to conduct extensive studies on the wheat grass both in experimental models and human subjects to develop wheat grass therapy with no side effects in prevention, cure and management of chronic diseases for which our modern systems have lost their hopes.